Introduction and Analysis of Five Urdu Verse Translations of the Holy Qur’ān - Assad Qayyum; Hafiz Muhammad Sajjad (Journal of Islamic and Religious Studies, 2018)
This research article gives a brief introduction and analysis of five Urdu translations of the Holy Qur’ān. Qur’ānic translations are an important source of learning and understanding of Qur’ān. In Urdu the translations of the Holy Book started in late 16th Century A.D. The number of these translations is in hundreds till now, which include translations in Urdu prose and verse. The first rhymed Urdu translation of the Holy Quran was written in the last quarter of 18th Century A.D. At present these translations are in hundreds, including complete as well as partial translations. Most of the translations are in rhymed form, while some are in free verse also. In this article five complete Holy Qur’ān translations have been discussed. Main aim of the article is to introduce the poets and their translations, as well as brief analysis of the translations. The translations are; Asar Zubairi Lakhnavi's "Sehr ul Bayan", Syed Shamim Rajz's "Aab e Rawaan", Seemab Akbar Abadi's "Wahi e Manzum", Abdul Aziz Khalid's "Furqan e Javed" and Qazi Ata ullah's "Mafhoom ul Quran". This article also explains how much the poets succeeded in presenting the message of Qur’ān. The merits and demerits of the translations have been highlighted. The article concludes that poetry, specially rhymed form, is not suitable for the translations of the Holy Book.